2018
DOI: 10.1021/acs.jchemed.7b00570
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Students with the Real World in a Green Organic Chemistry Laboratory Group Project: A Presentation and Writing Assignment in a Laboratory Class

Abstract: In the writing assignment and presentation described, small groups of students investigate a given industrial business/company that has made major changes to a synthesis, process, or procedure by implementing one or more of the 12 principles of green chemistry. Students submit a short paper on the assignment and present the project during the recitation portion of the laboratory. By studying an industrial change to a given synthesis or process, students become more aware of their environmental and global respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 57 publications
0
18
0
1
Order By: Relevance
“…Green chemistry has previously been integrated into organic chemistry education via inquiry-based laboratory experiments, course-based undergraduate research experiments, writing assignments, , lecture modules, student-generated presentations, , games, and outreach activities. , In fact, efforts to integrate green chemistry into the curriculum have been attempted at all levels: instructional, departmental, national, and global. At the instructional level, guidelines have been developed for integrating green chemistry into general and organic chemistry curriculums , and assessment .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Green chemistry has previously been integrated into organic chemistry education via inquiry-based laboratory experiments, course-based undergraduate research experiments, writing assignments, , lecture modules, student-generated presentations, , games, and outreach activities. , In fact, efforts to integrate green chemistry into the curriculum have been attempted at all levels: instructional, departmental, national, and global. At the instructional level, guidelines have been developed for integrating green chemistry into general and organic chemistry curriculums , and assessment .…”
Section: Introductionmentioning
confidence: 99%
“…This decision was founded on the premise that green chemistry is essential for the students' future careers, 1 helps facilitate systems thinking, 2−7 and introduces meaningful learning. 8,9 Green chemistry has previously been integrated into organic chemistry education via inquiry-based laboratory experiments, 10−19 course-based undergraduate research experiments, 20−22 writing assignments, 23,24 lecture modules, 25 student-generated presentations, 24,26 games, 27 and outreach activities. 28,29 In fact, efforts to integrate green chemistry into the curriculum have been attempted at all levels: instructional, departmental, national, and global.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This led us to develop a lecture project taken from elements of peer-based learning, role-play, gamification, and other elements of creative learning in chemistry. Students were assigned into groups, between 4 and 6 students per group, who worked a semester in lecture, meeting weekly to identify, develop, and present their proposed synthetic route, along with a business proposal and cost analysis in an entrepreneurial style pitch. This pitch is geared toward the faculty who role-play as mentors and investors.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the literature indicated that green chemistry had already been introduced into the curricula via laboratory experiments, apps, , games, systems thinking concept map extension (SOCME) visualizations, , Scrum methodology, and case studies. Indeed, the need to incorporate green chemistry has been recognized by professional societies such as the American Chemical Society, which provides guiding documents to aid in its implementation . Similarly, the nonprofit organization Beyond Benign has advocated the integration of green chemistry into education with its Green Chemistry Commitment .…”
Section: Introductionmentioning
confidence: 99%